Long‐term impacts from damming and water level manipulation on flow and salinity regimes in Lake Urmia, Iran. (28th May 2014) - Zeinoddini, Mostafa; Bakhtiari, Arash; Ehteshami, Majid
Abstract Lake Urmia in the north‐west of Iran is very large, very shallow and several times more saline than ocean water. The salinity of this terminal lake is of great ecological consequence for the existence and growth of Artemia Urmiana, a unique zooplankton endemic to the lake. It is a main food source for large bird populations. During the past decades, Lake Urmia has been strained by a number of anthropogenic and natural causes. They include extensive damming on the contributory rivers, building a dike‐type causeway and climate change. This paper deals with the long‐term impacts of damming, fresh water overexploitation and water level manipulation on flow and salinity conditions in Lake Urmia. For this purpose, the flow and salinity regimes were numerically simulated for the next four decades. The validity of the pseudo‐three‐dimensional hydrodynamic and advection‐dispersion models was assessed through sensitivity analysis of the models and comparing the simulated results against field measurements. The model predicted that because of damming on the rivers, the mean water level in the lake will possibly experience a drop of 2.2–2.8 m over next 40 years. The results indicated that, over decadal time periods, the lake most probably will be split into two interconnected smaller lakes. The northern lake was foreseen to become extremely saline, which will seriously threaten the Artemia's survival in this area. Over the long‐term periods, the southern lake seemed not to deviate much from its existing conditions. It however appeared to become more responsive to seasonal climatic changes and to the rivers inflow, as compared with its current conditions. Effects from climate changes were not considered in the current study.